High-flow nasal cannula oxygen therapy: physiological basis and clinical applications in anesthesia - Liu, Hui; Qu, Peng; Liu, Qian; Xiao, Fengfeng; Yang, Yanling; Xu, Liu; Zhang, Hongyan (Frontiers in Medicine, 2025)
High-flow nasal cannula (HFNC) oxygen therapy, a non-invasive respiratory support modality, has gained increasing attention for its advantages in perioperative care. This review outlines the basic components and key physiological effects of HFNC, including apneic oxygenation, positive end-expiratory pressure (PEEP), reduction of anatomical dead space, enhanced end-expiratory lung volume, accurate oxygen delivery, and active humidification. These mechanisms support its application across multiple perioperative phases, such as tracheal intubation, sedation for endoscopic procedures, upper airway surgeries, extubation, and recovery. HFNC has also shown promise in specific patient populations, including the obese, pregnant, and pediatric patients. Although its clinical benefits and safety profile are well-recognized, further studies are needed to clarify its indications, refine device settings, and explore its integration with other respiratory strategies. This review aims to summarize current clinical applications and recent developments of HFNC in anesthesia practice, providing both theoretical context and practical recommendations for its standardized use.